Dielectric Spectroscopy of Ferroelectric Crossbred PVDF–TiO2 Polymer Composite Thin Films - Arshad, A. H.; Dani, S.; Kulkarni, S. S.; Khadke, U. V. (Journal of Scientific Research, 2023)
Polyvinylidene fluoride (PVDF) ferroelectric polymer blend with titanium dioxide (TiO2) is synthesized in the form of thin films by solution casting method. The synthesized PVDF-TiO2 composite films with a different wt% of TiO2 (2, 4, 6, 8, and 10) as fillers in the PVDF matrix were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM) and Fourier Transform Infrared (FTIR) spectroscopy. The XRD patterns of PVDF-TiO2 composite films confirmed the existence of a β-phase PVDF, uniform distribution of TiO2 particles in the polymer matrix and the crystallinity of the polymer composites was found to be enhanced. The SEM micrograph depicts the augmentation in the structural density due to the addition of TiO2 particles in the PVDF matrix. The dielectric constant of the PVDF-TiO2films is found to be an anomaly at lower frequencies and decreases with an increase in frequency agreeing with the Maxwell–Wagner type of interfacial polarization. The enhancement in the dielectric constant of PVDF-TiO2 composites at lower frequencies suggests that the prepared polymer composite thin films are useful as separator membranes in energy storage devices.